Loss on The Stage: True West - Nisa Harika GÜZEL KÖŞKER (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
True West (1981) by Sam Shepard has been mostly reviewed as the theatricalization of conflicts arising from the differences between two brothers. Although the dramatic structure of the play rests on these clashing sides and transformations of the characters, the play equally unveils a melancholia triggered by the loss of the absent father and family unity. This melancholia can also be discerned on the transpersonal level in the loss of national ideals like mythic West after modern urbanization and industrialization. The mythic ideals threaded around the West gain more significance when considered in national context through the loss of ideal of paradise attributed by the European settlers to the American landscape and the United States of America as a burgeoning nation. Paralleling the personal and transpersonal levels, the feeling of loss is materialized in the acting out of repressed elements and through dialogues the two brothers have as if in a psychoanalytic session. This study hence aims to discuss the loss and melancholia embedded in these dialogues in light of psychoanalytic theory which offers critical perspectives in literary textual analyses.